2022
DOI: 10.1136/jech-2021-218278
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and COVID-19 diagnosis, hospitalisation and ICU admission among foreign-born and Swedish-born employees: a register-based study

Abstract: BackgroundResearch on occupation and risk of COVID-19 among foreign-born workers is lacking. We investigated whether working in essential occupations was associated with COVID-19 diagnosis, hospitalisation and intensive care unit (ICU) admission and whether foreign-born workers in similar occupations as Swedish-born individuals had a higher risk of the studied outcomes.MethodsOccupational data (2018–2019) of 326 052 employees (20–65 years) who were resident in Sweden as of 1 January 2020 were linked to COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
6
13
0
Order By: Relevance
“…Elevated infection risk in occupational groups with limited ability to work from home and those involving exposure to patients and/or the public echoes findings from the previous studies with more limited adjustment for potential confounding and from other global regions 1 2 3 4 5 12 13 . Across all analyses in the current study, adjustment for sociodemographic and health-related factors and non-work activities had limited impact on estimates.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Elevated infection risk in occupational groups with limited ability to work from home and those involving exposure to patients and/or the public echoes findings from the previous studies with more limited adjustment for potential confounding and from other global regions 1 2 3 4 5 12 13 . Across all analyses in the current study, adjustment for sociodemographic and health-related factors and non-work activities had limited impact on estimates.…”
Section: Discussionsupporting
confidence: 59%
“…Data from Germany 12 (February – September 2020) and Sweden 13 (January 2020 – February 2021) indicates elevated risk of infection amongst essential workers – including health, care, and service workers – compared to non-essential workers across the respective study periods, after adjustment for a range of socio-demographic factors. However, occupational differences in risk may vary by global region and comparative investigation for the UK is limited.…”
Section: Introductionmentioning
confidence: 99%
“…After excluding studies which contained duplicate patient data, 77 studies comprising over 200,000,000 confirmed COVID-19 cases were included. 4 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Data from Germany [ 12 ] (February – September 2020) and Sweden [ 13 ] (January 2020 – February 2021) indicated elevated risk of infection amongst essential workers – including health, care, and service workers – compared to non-essential workers across the respective study periods, after adjustment for a range of socio-demographic factors. However, occupational differences in risk may vary by global region and comparative investigation for the UK is limited.…”
Section: Introductionmentioning
confidence: 99%